The Perceptions of Husbands Regarding Early Marriage in Community Settings in Bengkulu, Indonesia: A Case-Control Study - Suyanto, Jipri; Adiningsih, Steyo; Isnawati, Rina; Lystia Poetranto, Anna; Rahmaida Puetri, Nona; Ibrahim Desem, Muhammad; Andriani Lienggonegoro, Lisa; Tan, Suriyani; Bima Prasetio, Diki; Susanty, Sri (YCAB Publisher, 2025)
Background:In Bengkulu, Indonesia, husbands’ views on early marriage are influenced by cultural norms. Many perceive early marriage as a rite of passage into adulthood, with family and community pressures encouraging them to marry young and assume the responsibility of providing for their families. However, young husbands often struggle to meet the financial and emotional demands of family life. Traditional gender roles further discourage them from seeking help, leading to increased stress. Engaging men in gender equality discussions and offering educational and career opportunities can help reduce the incidence of early marriage and foster healthier relationships. Objective:This study aims to examine the correlation between husbands’ perspectives and early marriage in the community setting of Bengkulu, Indonesia. Methods:This research employs a quantitative methodology with a case-control study design. Conducted in Bengkulu Province, the study included 892 respondents, divided into two groups: 669 in the case group and 223 in the control group, selected through multistage random sampling. The research was conducted over five months, from February to June 2024. Data were collected using questionnaires, and analysis was carried out through univariate, bivariate, and multivariate tests using Stata 17 as the analytical software. Results:In the case group, social stigma (COR: 6.4; 95%CI: 1.1-13.4; p-value: 0.0016) was significantly associated with husbands' perspectives. Other significant factors included ethnicity (COR: 6.3; 95%CI: 1.2-10.3; p-value: 0.026), quality of life (COR: 6.2; 95%CI: 2.1-13.2; p-value: 0.001), acceptable health literacy (COR: 5.7; 95%CI: 1.4-9.8; p-value: 0.001), and stress level (COR: 4.9; 95%CI: 1.3-7.9; p-value: 0.011). In the control group, the strongest correlation with husbands’ perspectives was stress (COR: 5.8; 95%CI: 2.1-12.5; p-value: 0.021), followed by quality of life (COR: 5.5; 95%CI: 1.2-12.7; p-value: 0.001), ethnicity (COR: 4.6; 95%CI: 1.3-11.2; p-value: 0.0003), moderate health literacy (COR: 4.5; 95%CI: 1.1-9.8; p-value: 0.001), and social stigma (COR: 4.3; 95%CI: 1.1-10.1; p-value: 0.013). Conclusion:In Bengkulu, Indonesia, young men face significant pressure to marry early due to cultural norms, societal expectations, and economic factors. While these early marriages fulfill traditional roles of providing and protecting, they often result in personal, emotional, and financial challenges for the husbands involved. Keywords:community; early marriage; husbands' perspectives; social stigma